Widespread aberrant functional connectivity throughout the whole brain in obstructive sleep apnea - Hou, Ailin; Pang, Xueming; Zhang, Xi; Peng, Yanmin; Li, Dongyue; Wang, He; Zhang, Quan; Liang, Meng; Gao, Feng (Frontiers in Neuroscience, 2022)
Objective: Previous neuroimaging studies have reported abnormal brain functional connectivity (FC) in patients of OSA that might contribute to their neurocognitive impairments. However, it is unclear whether OSA patients have a characteristic pattern of FC changes that can serve as a neuroimaging biomarker for identifying OSA. Method: Twenty-one OSA patients and twenty-one healthy controls were included in this study and scanned using resting-state fMRI. The automated anatomical labeling (AAL) atlas was used to divide the cerebrum into 90 regions and functional connectivity between each pair of regions was calculated. Univariate analyses were then performed to detect abnormal FC in OSA patients compared with controls, and multivariate pattern analyses (MVPA)were applied to classify between OSA patients and controls. Results: The univariate comparisons did not detect any significantly altered FC. However, the MVPA showed successful classification between OSA patients and controls with an accuracy of 83.33% (p=0.0001). Furthermore, the selected FCs were associated with nearly all brain regions and widely distributed in the whole brain, both within and between, many resting-state functional networks. Among these selected FCs, 3 were significantly correlated with the apnea-hypopnea index (AHI) and 2 with the percentage of time with saturation of oxygen below 90% during total sleep (%TST<90%). Conclusion: There existed widespread abnormal FCs in the whole brain in OSA patients. This aberrant FC pattern has the potential to serve as a neurological biomarker of OSA, highlighting its importance for understanding the complex neural mechanism underlying OSA and its cognitive impairment.